2000
DOI: 10.1021/ja000379p
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Origin of Metal Ion Rescue in the Hammerhead Ribozyme Reaction:  Mn2+-Assisted Redox Conversion of 2‘-Mercaptocytidine to Cytidine

Abstract: A specific oxygen atom in RNA is identified as a ligand for a metal ion when sulfur substitution of that atom shifts the metal ion specificity of the RNA-mediated process to a more thiophilic metal. Extensive discussion and debate have centered around whether a metal ion activates the 2′-oxygen nucleophile during the phosphotransesterification reaction catalyzed by the hammerhead ribozyme (HH). To test this possibility, we probed the metal ion specificity of HH reactions using a substrate that contained 2′-mer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…When those molecules are removed from the statistics, both DFTB3‐HNOP and DFTB3 systematically overestimate the proton affinities except the phosphorane set. Chemical modifications that involve the substitution of phosphoryl oxygens with sulfur represent important experimental probes to study metal ion binding and ribozyme mechanisms . Consequently, the modeling of pentavalent phosphorus both with and without thio substitutions is an important area that warrants attention in the development of next‐generation semiempirical quantum models for nucleic acid reactivity.…”
Section: Resultsmentioning
confidence: 99%
“…When those molecules are removed from the statistics, both DFTB3‐HNOP and DFTB3 systematically overestimate the proton affinities except the phosphorane set. Chemical modifications that involve the substitution of phosphoryl oxygens with sulfur represent important experimental probes to study metal ion binding and ribozyme mechanisms . Consequently, the modeling of pentavalent phosphorus both with and without thio substitutions is an important area that warrants attention in the development of next‐generation semiempirical quantum models for nucleic acid reactivity.…”
Section: Resultsmentioning
confidence: 99%
“…As a point in case, ribonucleotide reduction has been suggested to have been catalyzed by a ribozyme [ 12 ], but the suggestion has been met with considerable skepticism because of potential problems with free radicals in RNA molecules [ 13 ]. Hsiao et al [ 14 ] have reported redox catalysis by iron in a ribozyme and Hamm et al [ 15 ] have reported that Mn 2+ bound to the Hammerhead ribozyme is more active than Mg 2+ and that activity is affected by radical scavengers. These are indeed intriguing observations, suggesting that RNA may be more resilient to radicals and strong redox metals than hitherto assumed.…”
Section: Origin Of Ribonucleotide Reductionmentioning
confidence: 99%
“…The mobility of nucleic acids that carry thiophosphate monoesters is markedly diminished (evidence of strong interaction), while thiophosphate diesters showed no evidence of interaction. Disulfides also do not interact with the mercury in the APM gel matrix [19]. Under oxidizing conditions we observe a supershifted band migrating above nonthiophosphorylated RNA, but unretarded by the APM layer, consistent with dimer formation (data not shown).…”
Section: Resultsmentioning
confidence: 51%
“…When the sulfhydryl-reducing property of TCEP was used to investigate the metal ionbinding properties of the hammerhead ribozyme, this system gave the unexpected result that manganese assisted the redox conversion of 2 0 -mercaptocytidine to cytidine in the presence of TCEP [19]. Conversely, the stability of TCEP itself in the presence of nucleotides has not been previously explored.…”
mentioning
confidence: 99%